Beasts, savages, barbarians, idolaters, and infidels: racialization in the chronicles of the conquest of the Canary Islands. - Gil Hernández, Roberto (Postcolonial Studies, 2024)
Rereading the chronicles of the conquest of the Canary Islands in the present can be useful in assessing the role of racism in the foundation of the capitalist world system. From the perspective of historical sociology, this article finds that race does not operate in these chronicles as a marker of inequality, but racism does operate as an ideological justification for the violence inflicted on the Indigenous people of the islands. Through the study of the sources that narrate the surrender of the territory between the fifteenth and seventeenth centuries, a process of racialization is analyzed from the point of view of post-marxist and decolonial thought, that represents the Natives as inferior to the conquerors not only because of their physical appearance, but also because of cultural aspects such as their clothing, sexual behaviour, social order, or ways of producing knowledge. The article concludes by affirming that race as a concept does not precede racism, but rather that racism is the matrix of oppressions and privileges that the European colonial presence in the Canary archipelago fostered.